STRATEGI SEGMENTASI DAN DATABASE PERGURUAN TINGGI DALAM MENCIPTAKAN SDM PARIWISATA UNGGUL DAN BERKUALITAS (Studi Pada STIPRAM Yogyakarta) - Sulistyo, Agung; Yudiandri, Tri Eko; Ernawati, Hani; Djamil, Farah Diana; Mahanani, Sumiyar (Kepariwisataan: Jurnal Ilmiah, 2023)
Marketing Planning is essential to ensure that business activities generate profits. Segmentation and database implementation is one of the strategies that can be implemented in various business sectors, including education. Creating good graduates will affect the quality of management in the industrial world. Besides that, knowing the interests and preferences of prospective students is essential to produce graduates who meet expectations. This study aims to create a role model for developing superior and quality human resources in tourism. In addition, this study aims to determine the benefits students seek from Higher Education products. This study uses a qualitative descriptive research design emphasising the interaction between researchers and respondents. Data collection in this study used interview techniques and was distributed via Google form to 255 STIPRAM students. The results of segment mapping and the benefits sought by students were obtained based on the research conducted. Tourism-based universities, such as STIPRAM, can position themselves as the top choice universities. Further research could focus on the reasons and the extent of the benefits students seek.